Establishment of non-native Anoplophora horsfieldii (Coleoptera: Cerambycidae) in South Korea. Issue 1 (28th April 2023) - Lee, Seunghyun; Choi, Junhyeong; Jang, Hyunkyu; Choi, Woong; Kwon, Woochan; Kim, Doyoon; Gim, Jaedong; Park, Jonghyun; Park, Sangwook; Kim, Sangil; Shin, Seunggwan; Lee, Seunghwan
Abstract: The genus Anoplophora (Coleoptera: Cerambycidae) is among the most well-known insect genera in invasive entomology and is represented by 2 noted invasive alien species: the Asian longhorned beetle ( Anoplophora glabripennis (Motschulsky, 1854)) and the Citrus longhorned beetle ( Anoplophora chinensis (Forster, 1771)). In this study, a new non-native species belonging to the genus Anoplophora, Anoplophora horsfieldii (Hope, 1843), has been discovered on Jeju Island, South Korea (33°30′N, 126°30′E). Our field survey of the established area and potential habitats nearby identified numerous adult beetles and exit holes in its host, Celtis sinensis Persoon, 1805. This finding emphasizes the importance of continued monitoring and management of this new non-native species, which has the potential to cause significant ecological and economic damage.